2014
DOI: 10.1590/0102-311x00029313
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unprotected sexual practice among men and women with mental illnesses in Brazil

Abstract: Factors associated with unprotected sexual practice among men and women with mental illnesses in BrazilFatores associados com a prática do sexo desprotegido entre homens e mulheres com transtornos mentais no Brasil Los factores asociados con la práctica del sexo sin protección entre hombres y mujeres con trastornos mentales en Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Research has shown that psychiatric symptoms are often not the direct cause of sex risk behavior; instead, indirect socioeconomic factors like financial instability and partner violence [11] and individual characteristics such as substance use and attitudes toward sex [8, 10] may drive sex risk behavior. There are a number of effective interventions to reduce sex risk among this population in the short term, but research assessing sustained effects is needed [19, 20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research has shown that psychiatric symptoms are often not the direct cause of sex risk behavior; instead, indirect socioeconomic factors like financial instability and partner violence [11] and individual characteristics such as substance use and attitudes toward sex [8, 10] may drive sex risk behavior. There are a number of effective interventions to reduce sex risk among this population in the short term, but research assessing sustained effects is needed [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these researchers found that alcohol use was associated with HIV risk behavior, while demographic factors were not. In a national Brazilian sample of nearly 2,500 participants from inpatient psychiatric hospitals and community mental health clinics, half of whom had an SMI diagnosis, 60% of participants were sexually active in the past 6 months [11]. As with the Nigerian sample, high rates of HIV risk behaviors were reported among those who were sexually active, including 30% sex trading, 82% inconsistent condom use, and 26% multiple partners in the past 6 months.…”
Section: Primary Hiv Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender-based inequalities, including cultural values (e.g., men should have many partners, women should be monogamous), socioeconomic context (e.g. unequal access to education, employment, increased violence, and restricted reproductive rights among women) which potentially place women at a disadvantage for negotiating safer sex or refusing unwanted sex, can partially explain differential rates of unprotected sex reported among men and women [25].…”
Section: Depression As a Promoter Of Risk Behavior For Hivmentioning
confidence: 99%